BIOMASS PRODUCTION AND FORMULATION OF Bacillus subtilis FOR BIOLOGICAL CONTROL - Amran Muis (Indonesian Journal of Agricultural Science, 2006)
Bacillus subtilis is a widespread bacterium found in soil, water, and air. It controls the growth of certain harmful bacteria and fungi, presumably by competing for nutrients, growth sites on plants, and by directly colonizing and attaching to fungal pathogens. When applied to seeds, it colonizes the developing root system of the plants and continues to live on the root system and provides protection throughout the growing season. The study on biomass production and formulation of B. subtilis for biological control was conducted in the laboratory of Department of Plant Pathology, College of Agriculture, University of the Philippines Los Baños (UPLB-CA), College, Laguna from May to July 2005. The objective of the study was to determine the optimum pH and a good carbon source for biomass production of B. subtilis and to develop a seed treatment formulation of B. subtilis as biological control agent. Results showed that the optimum pH for growth of B. subtilis was pH 6 (1.85 x 109 cfu/ml). In laboratory tests for biomass production using cassava flour, corn flour, rice flour, and brown sugar as carbon sources, it grew best in brown sugar plus yeast extract medium (6.8 x 108 cfu ml-1 in sterile distilled water and 7.8 x 108 cfu ml-1 in coconut water). In test for bacterial biomass carriers, talc proved to be the best in terms of number of bacteria recovered from the seeds (3.98 x 105 cfu seed-1).